Soil–Plant Relationships in Soybean Cultivated under Crop Rotation after 17 Years of No-Tillage and Occasional Chiseling - Silva, Gustavo Ferreira da [UNESP]; Matusevicius, Ana Paula Oliveira [UNESP]; Calonego, Juliano Carlos [UNESP]; Chamma, Larissa [UNESP]; Luperini, Bruno Cesar Ottoboni [UNESP]; Alves, Michely da Silva [UNESP]; Leite, Hugo Mota Ferreira; Pinto, Elizabete de Jesus; Silva, Marcelo de Almeida [UNESP]; Putti, Fernando Ferrari [UNESP] (MDPI, 2022)
No-tillage cover crops contribute to better soil quality, being able to replace mechanized tillage management. This observation can only be made after several years of adopting conservationist practices and through research on soil–plant relationships. The objective of the research was to verify the relationship between the production components, physiological, root development, and physical-hydric properties of the soil in the yield of soybean grown in succession to different cover crops or with soil chiseling. The experiment was carried out in a randomized block design with four replications, comparing the cultivation of sunn hemp (Crotalaria juncea) and millet (Penninsetum glaucum L.) as cover crops and a treatment with soil chiseling. The evaluations were carried out during soybean (Glycine max L.) cultivation in the 2019/20 summer crop, that is, after 17 years of experimenting started in 2003. Rotation with sunn hemp increased soybean yield by 6% and 10%, compared with millet rotation and soil chiseling. The species used in crop rotation in a long-term no-tillage system interfere with the physical and water characteristics of the soil, affecting the physiological responses and soybean yield. The rotation with sunn hemp offers greater water stability to the plants and provides greater soybean yield in succession. Future research that better addresses year-to-year variation, architecture, and continuity of pores provided by crop rotation, and evaluations of gas exchange, fluorescence, and activities of stress enzymes in soybean plants may contribute to a better understanding of soil–plant relationships in long-term no-till.
Keywords: cover crops; Glycine max; plant physiology; root development; soil physics; soil water